2022
DOI: 10.1002/pssr.202200304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Electrodes on Surface Passivation of TiOx Selective Heterocontacts for Si Solar Cells

Abstract: This article presents a comprehensive study regarding the impact of the Al electrode on the surface passivation of three TiOx‐based passivating selective contacts: TiOx:Al/LiFx/Al,TiOx/LiFx/Al, and a‐Si/TiOx:Al/LiFx/Al. A deterioration in passivation is recorded after the deposition of the Al electrode at close to room temperature, where the deterioration correlated to the Al thickness. A thin Al (10 nm) electrode resulted in the most severe passivation decline, while samples with a 100 nm Al electrode showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…When Al capping layer is considered, PCD method becomes unsuitable to characterize the τ eff . Recently, Liang also found that fully metalized samples are not allowed the minority carrier lifetime to be measured with the PCD technique 44 . Therefore, here we characterize τ eff in the final device level by Suns‐ V OC measurement mode 45 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When Al capping layer is considered, PCD method becomes unsuitable to characterize the τ eff . Recently, Liang also found that fully metalized samples are not allowed the minority carrier lifetime to be measured with the PCD technique 44 . Therefore, here we characterize τ eff in the final device level by Suns‐ V OC measurement mode 45 .…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Liang also found that fully metalized samples are not allowed the minority carrier lifetime to be measured with the PCD technique. 44 Therefore, here we characterize τ eff in the final device level by Suns-V OC measurement mode. 45 Note that in this method, the τ eff does not only include the carrier recombination within the Si wafer and the electron-selective layer but also include the recombination beneath the front electrodes, hole-selective layer, and the Al capping layer.…”
Section: Resultsmentioning
confidence: 99%
“…Second, it must be noted that all of the passivation parameters reported in Table are for prior metallization. It has been demonstrated that the adverse influence of metallization (Al) on the passivation quality is a common concern for all TiO x -based contacts, which imposes a reduced V oc compared with i V oc at the cell level. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Liang also found that fully metalized samples are not allowed the minority carrier lifetime to be measured with the PCD technique. 43 Therefore, here we characterizeτ eff in final device level by Suns-V oc measurement mode. 44 Figure 2c shows that theτ eff increases with post-annealing temperature (within 300 °C), again demonstrating that the passivation effect is improved by post-annealing treatment.…”
Section: Resultsmentioning
confidence: 99%